A Review Paper on GIS Web-System to Support Emergency Situations in Urban Areas and Provide Services - Swapnil R, Rajput; Kale, KV (International Journal of Computer Sciences and Engineering, 2015)
The agility measure and time response during the emergency situation is that hour when the incident has existed. Prune the risk of losing lives & property from appropriate response at emergency place. Therefore this paper-thin determine and inspect the concurrent android petition, GIS and web-base system that is focusing with prior information of inspected dataset. Purpose of the system is intended in case of emergency in organizations and society. Emergency incorporates accidental, health care, fire platoons, external emergency (storm, floods, and earthquake). The person in an emergency or anybody at the emergency place will send his current location from smart phone gadget; geo-location coordinates dispatch on each supplication onto the server. The proposed petition will respond to proper request from client.